Investigating Influence of Different Materials on Window Thermal Performance - Sangrutsamee, Vachira; Sripanom, Tanut (Journal of Architectural/Planning Research and Studies (JARS), 2015)
This study is an experimental research study in order to find the effectiveness of the heat transfer and to compare the temperature behaviors of the windows with different layers made of various materials. The windows were divided into four types: 1) clear glass window with aluminum frames, 2) clear glass window with wooden frames, 3) wooden window, and 4) double layered window with a clear glass and aluminum sliding window (the inner layer) and a wooden louvered window (the outer layer). In this study, the heat transfer values of the materials were analyzed. The temperatures of the air and material surfaces were checked. The size of the created prototype was 1.00 x 0.50 meters installed in the test box that had foam insulation on its five sides. Data were recorded for 24 hours. The results show that the heat resistance of the wooden materials was approximately 1.4 times higher than the glass materials. The air temperatures inside all test boxes were higher than that of the surrounding air. The highest air temperatures inside the test boxes were 36.5 - 56.7 °C during 01.00 p.m. – 02.40 p.m. The lowest air temperature was 25 °C at 06.00 a.m. The clear glass window with aluminum frames had the highest temperature in the test box and the highest difference between the temperatures at day and night. The double layered window had the lowest difference. Finally, it can be concluded that the double layered window could effectively protect heat transferring into the buildings, reduce the cooling load, and facilitate energy conservation